(untitled) (Tanzania Journal for Population studies and Development, 2019)
Since the 1994 International Conference on Population and Development (ICPD) in Cairo (1994) and the 1995 Fourth World Conference on Women in Beijing there has been an increasing consensus on the importance of involving men in reproductive health care. This paper analysed male perception of involvement and their roles in productive health in a study that was conducted in 2015 and used the Tanzania Demographic and Health Survey (TDHS) to compliment the empirical data. Findings show male still perceive themselves main decision makers on reproductive health issues. Their roles were mainly centred on decision making on matters of reproductive health including family planning. About sixty-one percent (60.6 percent) indicated that decision about sex has to be done by men. On the use of family planning, more than seventy percent (72.4 percent) indicated that men are the ones to make such decision. The study established that while 78.7 percent of the respondents approves of family planning, less than fifty percent (43 percent) indicated that they discuss family planning issues with their spouse. This further demonstrates that men are main decision makers on issues of reproductive health. Analysis of their knowledge on reproductive health, using DHS data indicate that about 100% were informed of at least one family planning method and that the majority get information from authentic sources including radio, television and newspapers. Based on the results and understating that knowledge of men’s own perception is critical for both pragmatic and policy interventions, it is recommended that deliberate efforts need to continue to have men change their perceptions and become equal partners in reproductive health for the benefit of the family and society at large.